Assessment of Almond (Prunus dulcis L.) for Self-Compatibility and Stigma Receptivity Period Based on Fruit Set Index - Kawsar, Yasin; Abid, Hakimullah; Mukhlis, Naseer; Mangal, Saifullah (Journal for Research in Applied Sciences and Biotechnology, 2023)
Regarding to the self-compatibility test the 6 genotypes under the study show low self-fertilization and categorized in self-incompatible group, in evaluating the best time for hand pollination, the emasculated genotypes in the same day show significantly difference in responding to the hand pollination in the days After emasculation which the highest fruit set percentage recorded in 3 days after emasculation and decreased in other days when considering the 0 day to 8 days after emasculation the study shows the importance and emphasis of choosing the overlapping varieties in an orchard and considering the self- incompatibility of genotypes and pollinator in reform and development of new almond orchard.